Method for preparing graphene composite porous silicon-copper alloy negative electrode material by taking waste lithium battery negative electrode powder as raw material
By preparing graphene composite porous silicon copper alloy material from the graphite negative electrode powder of waste lithium battery, the problem of unused graphite negative electrode and volume expansion of silicon-based negative electrode is solved, efficient resource recycling and cost reduction are achieved, and lithium-ion batteries are used to achieve lithium-ion batteries. The update and iteration of the negative electrode material provides support.
Patent Information
- Application Number
- CN202411244740.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The graphite negative electrode of the used lithium battery has not been properly handled, and the silicon-based negative electrode has not been widely popularized due to volume expansion problems. The existing technology is costly and has poor results.
The graphene composite porous silicon copper alloy negative electrode material was prepared by using the scrap lithium battery graphite negative electrode powder, and the Cu6.69Si alloy was made by delimiting the ethanol solution and treated with H2O2, and then grinding it with copper powder and nano-silicon balls to form a Cu6.69Si alloy, combining polydiallyl group Dimethyl ammonium chloride (PDDA) is dispersed ultrasonically to form porous Cu6.69Si/graphene powder, solving the problem of silicon volume expansion and improving conductivity.
It realizes the high-value utilization of graphite anode of waste lithium batteries, reduces the production cost of silicon-based anode materials, provides a new solution for silicon-based volume expansion, and provides support for environmental protection and the update and iteration of lithium-ion battery anode materials. .
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for high-value utilization of waste lithium-ion battery graphite negative electrodes. Background Art
[0002] In recent years, with the depletion of fossil energy and the pressure of environmental protection, more and more new energy vehicles have been put into the market. New energy vehicles have developed rapidly in the past decade. For example, the global new energy vehicle ownership reached 5 million in 2018, an increase of 63% compared with 2017. It is estimated that by 2040, new energy vehicles will account for 11.28% of the total number of vehicles. It can be inferred that the demand for lithium-ion batteries in the future automotive market will also increase sharply. Lithium-ion batteries will have to face the problem of retirement after a certain number of years of use. If retired lithium-ion batteries are not properly handled, the heavy metals that seep out of the negative electrode materials will continue to migrate with the atmosphere, water, and soil, or be converted into more toxic compounds, causing water and soil pollution. The decomposition and hydrolysis products of electrolyte solvents and binders will cause organic pollution such as aldehydes, ketones, and methanol. Heavy metals and organic matter that enter the ecosystem are enriched in higher organisms through the food chain, causing great harm to the ecosystem and human health. Among the many negative electrode materials for lithium batteries, graphite is regarded as an ideal negative electrode material for lithium-ion batteries due to its excellent rate performance and cycle stability. Its market share is increasing, and the number of retired batteries is also surging. The graphite negative electrodes of retired lithium-ion batteries are often not properly handled. Most of the retired graphite negative electrode sheets are recycled after the graphite is removed, and the graphite is treated as solid waste. In lithium-ion batteries, the graphite negative electrode accounts for 25% to 35% of the total mass. If such a large amount of graphite negative electrodes can be used at a high value, it will not only make the company profitable, but also protect the environment.
[0003] Silicon-based negative electrodes (4200mAh / g) have a theoretical capacity far exceeding that of carbon-based negative electrodes (372mAh / g), so they are also considered to be the negative electrode materials for the next generation of lithium-ion batteries. However, due to the volume expansion problem of silicon-based negative electrodes during the battery charging and discharging process, they have not been widely popularized. At present, in order to solve the problem of volume expansion of silicon-based negative electrodes, the common practice is to use carbon sources such as asphalt to coat the silicon surface to alleviate the volume expansion, but this approach is not effective and has high costs. Summary of the invention
[0004] The present invention aims to solve the technical problem that the negative electrode graphite of waste lithium batteries is currently treated as solid waste and the volume of the existing silicon-based negative electrode expands, and provides a method for preparing a graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material.
[0005] The method of the present invention for preparing a graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material is carried out according to the following steps: 1. Discharge the used lithium-ion battery to 3.2-3.7V through the battery charging and discharging system; 2. dismantling the waste lithium-ion battery obtained in step 1 and taking out the waste lithium-intercalated graphite negative electrode; 3. Soak the waste lithium-intercalated graphite negative electrode obtained in step 2 in an ethanol solution for 30 minutes to 1 hour. The lithium in the graphite reacts with the hydroxyl group in the ethanol solution to generate hydrogen, so that the graphite is freed from the interlayer force, and finally a multilayer graphene slurry and copper foil are obtained.
[0006] The ethanol volume concentration in the ethanol solution is 1-99%; 4. Add H2O2 solution to the multilayer graphene slurry obtained in step 3 and stir for 10-30 minutes to obtain a graphene oxide dispersion.
[0007] The volume concentration of H2O2 in the H2O2 solution is 1-30%; The volume ratio of the mass of graphene oxide to water in the graphene oxide dispersion is 1 mg: (3 mL to 4 mL); 5. The copper foil obtained in step 3 is crushed, and then copper powder is prepared by high-energy ball milling; the copper powder and powdered nano-silicon are evenly ball-milled for 30 min to 35 min; the mixture is placed in a tube furnace, and allowed to stand at room temperature for 20 min to 25 min under an inert atmosphere with a flow rate of 50 mL / min to 55 mL / min, and then calcined at 300°C to 900°C for 3 h to 8 h in an inert atmosphere to obtain Cu3Si and Cu 6.69 The obtained silicon-copper alloy is washed with concentrated nitric acid to remove CuSi3 and leave Cu 6.69 Si, and then washed with water and dried to obtain nanoporous Cu 6.69 Si silicon copper alloy particles; The mass ratio of the copper powder to the powdered nano-silicon is 3:(2-2.5); 6. ①: The nanoporous Cu obtained in step 4 6.69 Porous Cu was obtained by ultrasonically dispersing Si particles and polydiallyldimethylammonium chloride (PDDA) aqueous solution in deionized water. 6.69 Si / PDDA aqueous solution; The mass fraction of the polydiallyldimethylammonium chloride aqueous solution is 20% to 22%; The nanoporous Cu obtained in step 4 6.69 The mass ratio of Si particles to the volume of polydiallyldimethylammonium chloride aqueous solution is (200 mg~210 mg):1 mL; The volume ratio of the polydiallyldimethylammonium chloride aqueous solution to the solvent deionized water is 1:(40-44); 7. Take the porous Cu obtained in step 6 6.69 The Si / PDDA aqueous solution was poured into the graphene oxide dispersion obtained in step 4 and ultrasonically dispersed to obtain a porous Cu 6.69 Si-PDDA-graphene oxide solution; The graphene oxide dispersion and the porous Cu obtained in step six 6.69 Si / PDDA aqueous solution equal volume; 8. The porous Cu obtained in step 7 6.69 The Si-PDDA-graphene oxide solution was freeze-dried to obtain porous Cu 6.69 Si-PDDA-graphene oxide powder was then placed in a tube furnace and allowed to stand at room temperature for 20 min to 25 min in an inert atmosphere with a flow rate of 50 mL / min to 55 mL / min, and then calcined at 300 °C to 900 °C for 3 h to 8 h in an inert atmosphere to obtain porous Cu 6.69 Si / graphene powder.
[0008] In step 5 of the present invention, nanoporous Cu is obtained. 6.69 There is a silicon oxide layer on the surface of Si particles, which makes the nanoporous silicon particles negatively charged, providing conditions for the subsequent use of the electrostatic adsorption principle to combine graphene with them.
[0009] The porous Cu obtained in step eight of the present invention 6.69 The Cu in Si / graphene powder can improve the conductivity of the particles and solve the problem of poor conductivity of pure silicon. The electrochemically inert copper can also serve as a skeleton to alleviate the volume expansion of silicon during the charging and discharging process. The outer graphene framework can also help alleviate the problem of silicon volume expansion.
[0010] The present invention makes the graphite negative electrode of waste lithium ion battery into porous Cu 6.69 Si / graphene negative electrode materials can realize the resource recycling of waste lithium-ion battery graphite negative electrodes and reduce the production cost of silicon-based negative electrode materials. This is of great significance for environmental protection and promoting the updating and iteration of lithium-ion battery negative electrode materials.
[0011] The present invention has the following advantages and positive significance: 1. The present invention can make high-value use of graphite negative electrodes of waste lithium-ion batteries, which is of great significance for protecting the environment and saving resources; 2. The electrostatic adsorption packaging process adopted by the present invention is simple and can be applied to industry on a large scale; 3. The present invention provides a new idea and solution for solving the problem of silicon-based volume expansion. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 The XRD characterization diagram of the graphite directly scraped from the discarded lithium-intercalated graphite negative electrode in step 2 of experiment 1 and the few-layer graphene obtained by freeze-drying the graphene dispersion obtained in step 4; Figure 2 The SEM image of the few-layer graphene oxide obtained by freeze-drying the graphene dispersion obtained in step 4 of experiment 1; Figure 3 The silicon-copper alloy and nanoporous Cu prepared in step 5 of experiment 1 6.69 XRD characterization diagram of Si silicon copper particles; Figure 4 This is the SEM characterization image of the silicon-copper alloy prepared in step 5 of experiment 1; Figure 5 The nanoporous Cu prepared in step 5 of experiment 1 6.69 TEM characterization of Si particles.
[0013] Figure 6 The nanoporous Cu prepared in step 5 of experiment 1 6.69 SEM image of Si particles; Figure 7 The porous Cu prepared in step 8 of experiment 1 6.69 TEM image of Si / graphene powder. DETAILED DESCRIPTION
[0014] Specific implementation method 1: This implementation method is a method for preparing a graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material, which is specifically carried out in the following steps: 1. Discharge the used lithium-ion battery to 3.2-3.7V through the battery charging and discharging system; 2. dismantling the waste lithium-ion battery obtained in step 1 and taking out the waste lithium-intercalated graphite negative electrode; 3. Soak the waste lithium-intercalated graphite negative electrode obtained in step 2 in an ethanol solution for 30 minutes to 1 hour. The lithium in the graphite reacts with the hydroxyl group in the ethanol solution to generate hydrogen, so that the graphite is freed from the interlayer force, and finally a multilayer graphene slurry and copper foil are obtained.
[0015] The ethanol volume concentration in the ethanol solution is 1-99%; 4. Add H2O2 solution to the multilayer graphene slurry obtained in step 3 and stir for 10-30 minutes to obtain a graphene oxide dispersion.
[0016] The volume concentration of H2O2 in the H2O2 solution is 1-30%; The volume ratio of the mass of graphene oxide to water in the graphene oxide dispersion is 1 mg: (3 mL to 4 mL); 5. The copper foil obtained in step 3 is crushed, and then copper powder is prepared by high-energy ball milling; the copper powder and powdered nano-silicon are evenly ball-milled for 30 min to 35 min; the mixture is placed in a tube furnace, and allowed to stand at room temperature for 20 min to 25 min under an inert atmosphere with a flow rate of 50 mL / min to 55 mL / min, and then calcined at 300°C to 900°C for 3 h to 8 h in an inert atmosphere to obtain Cu3Si and Cu 6.69 The obtained silicon-copper alloy is washed with concentrated nitric acid to remove Cu3Si and leave Cu 6.69 Si, and then washed with water and dried to obtain nanoporous Cu 6.69 Si silicon copper alloy particles; The mass ratio of the copper powder to the powdered nano-silicon is 3:(2-2.5); 6. ①: The nanoporous Cu obtained in step 4 6.69 Porous Cu was prepared by ultrasonically dispersing Si particles and polydiallyldimethylammonium chloride (PDDA) aqueous solution in deionized water. 6.69 Si / PDDA aqueous solution; The mass fraction of the polydiallyldimethylammonium chloride aqueous solution is 20% to 22%; The nanoporous Cu obtained in step 4 6.69 The mass ratio of Si particles to the volume of polydiallyldimethylammonium chloride aqueous solution is (200 mg~210 mg):1 mL; The volume ratio of the polydiallyldimethylammonium chloride aqueous solution to the solvent deionized water is 1:(40-44); 7. Take the porous Cu obtained in step 6 6.69 The Si / PDDA aqueous solution was poured into the graphene oxide dispersion obtained in step 4 and ultrasonically dispersed to obtain a porous Cu 6.69 Si-PDDA-graphene oxide solution; The graphene oxide dispersion and the porous Cu obtained in step six 6.69 Si / PDDA aqueous solution equal volume; 8. The porous Cu obtained in step 7 6.69 The Si-PDDA-graphene oxide solution was freeze-dried to obtain porous Cu 6.69 Si-PDDA-graphene oxide powder was then placed in a tube furnace and allowed to stand at room temperature for 20 min to 25 min in an inert atmosphere with a flow rate of 50 mL / min to 55 mL / min, and then calcined at 300 °C to 900 °C for 3 h to 8 h in an inert atmosphere to obtain porous Cu 6.69 Si / graphene powder.
[0017] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the rotation speed of the copper powder and the powdered nano-silicon ball mill in step 5 is 8000 rpm. The rest is the same as the specific embodiment 1.
[0018] The present invention is verified by the following tests: Experiment 1: A method for preparing a graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material, specifically carried out in the following steps: 1. Discharge the used lithium-ion battery to 3.7V through the battery charging and discharging system; 2. dismantling the waste lithium-ion battery obtained in step 1 and taking out the waste lithium-intercalated graphite negative electrode; 3. Soak the waste lithium-intercalated graphite negative electrode obtained in step 2 in an ethanol solution for 30 minutes. The lithium in the graphite reacts with the hydroxyl group in the ethanol solution to generate hydrogen, so that the graphite is freed from the interlayer force, and finally a multilayer graphene slurry and copper foil are obtained.
[0019] The ethanol volume concentration in the ethanol solution is 50%; 4. Add H2O2 solution to the multilayer graphene slurry obtained in step 3 and stir for 10 minutes to obtain graphene oxide dispersion.
[0020] The volume concentration of H2O2 in the H2O2 solution is 20%; The mass ratio of graphene oxide to water in the graphene oxide dispersion is 1 mg:3 mL; 5. The copper foil obtained in step 3 is crushed, and then copper powder is prepared by high-energy ball milling; the copper powder and powdered nano-silicon are evenly ball-milled for 30 min; the mixture is placed in a tube furnace, and allowed to stand at room temperature for 20 min under an inert atmosphere with a flow rate of 50 mL / min, and then calcined at 300 ° C for 3 h in an inert atmosphere to obtain Cu3Si and Cu 6.69 The obtained silicon-copper alloy is washed with concentrated nitric acid to remove Cu3Si and leave Cu 6.69 Si, and then washed with water and dried to obtain nanoporous Cu 6.69 Si silicon copper alloy particles; The mass ratio of the copper powder to the powdered nano-silicon is 3:2; 6. ①: The nanoporous Cu obtained in step 4 6.69 Porous Cu was obtained by ultrasonically dispersing Si particles and polydiallyldimethylammonium chloride (PDDA) aqueous solution in deionized water. 6.69 Si / PDDA aqueous solution; The mass fraction of the polydiallyldimethylammonium chloride aqueous solution is 20%; The nanoporous Cu obtained in step 4 6.69 The mass ratio of Si particles to the volume of polydiallyldimethylammonium chloride aqueous solution was 200 mg:1 mL; The volume ratio of the polydiallyldimethylammonium chloride aqueous solution to the solvent deionized water is 1:40; 7. Take the porous Cu obtained in step 6 6.69 The Si / PDDA aqueous solution was poured into the graphene oxide dispersion obtained in step 4 and ultrasonically dispersed to obtain a porous Cu 6.69 Si-PDDA-graphene oxide solution; The graphene oxide dispersion and the porous Cu obtained in step six 6.69 Si / PDDA aqueous solution equal volume; 8. The porous Cu obtained in step 7 6.69 The Si-PDDA-graphene oxide solution was freeze-dried to obtain porous Cu 6.69 The Si-PDDA-graphene oxide powder was then placed in a tube furnace and allowed to stand at room temperature for 20 min in an inert atmosphere with a flow rate of 50 mL / min, and then calcined at 300 °C in an inert atmosphere for 3 h to obtain porous Cu 6.69 Si / graphene powder.
[0021] Figure 1 It is the XRD characterization diagram of the graphite directly scraped from the discarded lithium-intercalated graphite negative electrode in step 2 of experiment 1 and the few-layer graphene oxide obtained by freeze-drying the graphene dispersion obtained in step 4. SG is the graphite separated in step 2 of experiment 1, and GO is the few-layer graphene oxide obtained by freeze-drying the graphene dispersion obtained in step 4 of experiment 1. It can be seen that the generated hydrogen expands the graphite, and the spacing between graphite layers increases after oxidation treatment with H2O2 solution, gradually forming a single layer or multi-layer graphene oxide.
[0022] Figure 2 This is the SEM image of the few-layer graphene oxide obtained by freeze-drying the graphene dispersion obtained in step 4 of experiment 1. It can be seen that the prepared graphene oxide is a single layer and is relatively complete.
[0023] Figure 3 This is the XRD characterization diagram of the silicon-copper alloy and nanoporous silicon particles prepared in step five of experiment one. It can be seen that the copper of the silicon-copper alloy made of nano-silicon powder and copper powder is completely removed after acid washing, and the silicon-copper alloy is mainly composed of Cu3Si and Cu6.69Si.
[0024] Figure 4 This is the SEM characterization image of the silicon-copper alloy prepared in step five of experiment one.
[0025] Figure 5This is the TEM characterization image of the nanoporous Cu6.69Si particles prepared in step five of experiment one. It can be seen that there is a silicon oxide layer with a thickness of about 20nm~40nm on its surface. This oxide layer makes the nanoporous silicon particles negatively charged, which provides conditions for the subsequent use of the electrostatic adsorption principle to combine graphene with them.
[0026] Figure 6 This is the SEM image of the nanoporous Cu6.69Si particles prepared in step 5 of experiment 1. It can be seen that after the silicon-copper alloy is washed with nitric acid to remove Cu3Si, the silicon material presents a honeycomb-like porous structure. These gaps can be porous Cu 6.69 The volume expansion of Si / graphene negative electrode materials during the charging and discharging process provides buffer space, and the Cu skeleton can also increase the conductivity and stability of the material.
[0027] Figure 7 The porous Cu prepared in step 8 of experiment 1 6.69 The TEM image of Si / graphene powder shows that a layer of graphene is wrapped on the surface of porous silicon. Due to the ductility and excellent mechanical properties of graphene, it provides a firm and tough skeleton for the porous silicon inside. This is another guarantee for the silicon-based negative electrode material to alleviate volume expansion during the charging and discharging process.
Claims
1. A method for preparing a graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material, characterized in that The method for preparing graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material is carried out in the following steps:
1. Discharge the used lithium-ion battery to 3.2-3.7V through the battery charging and discharging system; 2. dismantling the waste lithium-ion battery obtained in step 1 and taking out the waste lithium-intercalated graphite negative electrode; 3. Soak the waste lithium-intercalated graphite negative electrode obtained in step 2 in an ethanol solution for 30 minutes to 1 hour. The lithium in the graphite reacts with the hydroxyl group in the ethanol solution to generate hydrogen, so that the graphite is freed from the interlayer force, and finally a multilayer graphene slurry and copper foil are obtained.
2. The ethanol volume concentration in the ethanol solution is 1-99%; 4. Add H2O2 solution to the multilayer graphene slurry obtained in step 3 and stir for 10-30 minutes to obtain a graphene oxide dispersion.
3. The volume concentration of H2O2 in the H2O2 solution is 1-30%; The volume ratio of the mass of graphene oxide to water in the graphene oxide dispersion is 1 mg: (3 mL to 4 mL); 5. The copper foil obtained in step 3 is crushed, and then copper powder is prepared by high-energy ball milling; the copper powder and powdered nano-silicon are evenly ball-milled for 30 min to 35 min; the mixture is placed in a tube furnace, and allowed to stand at room temperature for 20 min to 25 min under an inert atmosphere with a flow rate of 50 mL / min to 55 mL / min, and then calcined at 300°C to 900°C for 3 h to 8 h in an inert atmosphere to obtain Cu3Si and Cu 6.69 The obtained silicon-copper alloy is washed with concentrated nitric acid to remove Cu3Si and leave Cu 6.69 Si, and then washed with water and dried to obtain nanoporous Cu 6.69 Si silicon copper alloy particles; The mass ratio of the copper powder to the powdered nano-silicon is 3:(2-2.5); 6. ①: The nanoporous Cu obtained in step 4 6.69 Porous Cu was prepared by ultrasonically dispersing Si particles and polydiallyldimethylammonium chloride (PDDA) aqueous solution in deionized water. 6.69 Si / PDDA aqueous solution; The mass fraction of the polydiallyldimethylammonium chloride aqueous solution is 20% to 22%; The nanoporous Cu obtained in step 4 6.69 The mass ratio of Si particles to the volume of polydiallyldimethylammonium chloride aqueous solution is (200 mg~210 mg):1 mL; The volume ratio of the polydiallyldimethylammonium chloride aqueous solution to the solvent deionized water is 1:(40-44); 7. Take the porous Cu obtained in step 6 6.69 The Si / PDDA aqueous solution was poured into the graphene oxide dispersion obtained in step 4 and ultrasonically dispersed to obtain a porous Cu 6.69 Si-PDDA-graphene oxide solution; The graphene oxide dispersion and the porous Cu obtained in step six 6.69 Si / PDDA aqueous solution equal volume; 8. The porous Cu obtained in step 7 6.69 The Si-PDDA-graphene oxide solution was freeze-dried to obtain porous Cu 6.69 Si-PDDA-graphene oxide powder was then placed in a tube furnace and allowed to stand at room temperature for 20 min to 25 min in an inert atmosphere with a flow rate of 50 mL / min to 55 mL / min, and then calcined at 300 °C to 900 °C for 3 h to 8 h in an inert atmosphere to obtain porous Cu 6.69 Si / graphene powder.
4. The method for preparing a graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material according to claim 1, characterized in that In step 5, the copper foil is crushed by using scissors or a crusher.
5. The method for preparing a graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material according to claim 1, characterized in that In step 5, the rotation speed of the copper powder and powdered nano-silicon ball mill is 8000 rpm.
6. The method for preparing a graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material according to claim 1, characterized in that The inert atmosphere described in step 5 is argon.
7. The method for preparing a graphene composite porous silicon-copper alloy negative electrode material using waste lithium battery negative electrode powder as raw material according to claim 1, characterized in that The inert atmosphere described in step eight is argon.
Citation Information
Patent Citations
Keggin type heteropoly acid functionalized graphene loaded nano copper particle modified electrode and application thereof
CN103913493A
Preparation method and application of novel silicon-based composite porous negative electrode material of lithium ion battery
CN112885997A
Method for preparing nitrogen-doped porous reduced graphene oxide from recycled negative electrode graphite materials of waste lithium ion batteries
CN113651320A
Preparation method of three-dimensional structure electrode without conductive agent and binder
CN115132972A
Lithium Ion Battery Anode Containing Silicon Nanowires Grown in situ in Pores of Graphene Foam and Production Process
US20180102543A1